2009
DOI: 10.1105/tpc.109.067785
|View full text |Cite
|
Sign up to set email alerts
|

The PLASTID DIVISION1 and 2 Components of the Chloroplast Division Machinery Determine the Rate of Chloroplast Division in Land Plant Cell Differentiation  

Abstract: In most algae, the chloroplast division rate is held constant to maintain the proper number of chloroplasts per cell. By contrast, land plants evolved cell and chloroplast differentiation systems in which the size and number of chloroplasts change along with their respective cellular function by regulation of the division rate. Here, we show that PLASTID DIVISION (PDV) proteins, land plant-specific components of the division apparatus, determine the rate of chloroplast division. Overexpression of PDV proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(178 citation statements)
references
References 53 publications
(95 reference statements)
9
165
2
Order By: Relevance
“…Growth of the wild type with 1 mM BA results in a 1.41-fold increase in the chloroplast number per cell (Fig. 8B), consistent with a cytokinin effect on chloroplast division (Okazaki et al, 2009). Although the chloroplast number per cell of the gnc cga1 mutant is similar to that of the wild type in the untreated sample, it exhibits reduced sensitivity to cytokinin, resulting in significantly lower numbers of chloroplasts than the wild type in the presence of 1 mM BA (1.25-fold cytokinin-dependent increase in chloroplast number per cell for gnc cga1 compared with 1.41-fold increase for the wild type; Fig.…”
Section: Effect Of Cytokinin On Chloroplast Division In Mutants Of Thsupporting
confidence: 69%
See 3 more Smart Citations
“…Growth of the wild type with 1 mM BA results in a 1.41-fold increase in the chloroplast number per cell (Fig. 8B), consistent with a cytokinin effect on chloroplast division (Okazaki et al, 2009). Although the chloroplast number per cell of the gnc cga1 mutant is similar to that of the wild type in the untreated sample, it exhibits reduced sensitivity to cytokinin, resulting in significantly lower numbers of chloroplasts than the wild type in the presence of 1 mM BA (1.25-fold cytokinin-dependent increase in chloroplast number per cell for gnc cga1 compared with 1.41-fold increase for the wild type; Fig.…”
Section: Effect Of Cytokinin On Chloroplast Division In Mutants Of Thsupporting
confidence: 69%
“…S10). The effects of GNC/CGA1 on cell expansion are likely related to their role in the repression of GA signaling (Richter et al, 2010), while their effects on chloroplast size suggest a role in the regulation of chloroplast division (Okazaki et al, 2009). The effect of GNC on chloroplast size and division provides an explanation, at least in part, for the greater number of chloroplasts reported in leaves of GNC overexpression lines (Hudson et al, 2011).…”
Section: Increases In Chloroplast Biogenesis Can Be Regulated Postembmentioning
confidence: 99%
See 2 more Smart Citations
“…In Arabidopsis, we analyzed the expression of chloroplast division factors known to alter chloroplast number, including plastid division and accumulation and replication of cholorplast genes (Miyagishima et al, 2006;Glynn et al, 2008;Okazaki et al, 2009). However, these genes are not expressed in a similar fashion (Jen et al, 2006) and were not found to be significantly altered in Arabidopsis CGA1 transgenic lines (Hudson et al, 2011).…”
Section: Cga1 Modifies the Expression Of Important Chloroplast-localimentioning
confidence: 99%